2021
DOI: 10.1016/j.scog.2021.100209
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic and neurocognitive correlates of probabilistic classification learning in schizophrenia

Abstract: Individuals with schizophrenia demonstrate impaired implicit learning on cognitively complex tasks and preserved implicit motor learning. However, little is known about how implicit learning may be related to other linguistic and cognitive variables, including development of complex language including comprehension and syntax. This study explored the relationship between probabilistic classification learning, a type of implicit learning style, and linguistic and cognitive skills in schizophrenia. This was done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Although several studies have questioned the view that the WPT implicates primarily non-declarative learning and memory processes ( Knowlton et al, 1996a ; Poldrack et al, 2001 ; Gluck et al, 2002 ; Hopkins et al, 2004 ; Foerde et al, 2006 , 2007 ; Lagnado et al, 2006 ; Meeter et al, 2006 ; Newell et al, 2007 ; Price, 2009 ; Li et al, 2016 ), numerous studies evaluating the learning capacities of various clinical populations were conceived with the notion that the WPT assesses striatum-dependent or procedural learning. Indeed, the WPT or the Ice Cream Task, a modified version of the WPT in which participants must predict the flavor of ice cream preferred by a cartoon figure based on the different accessories worn by that figure ( Shohamy et al, 2004a ), have been extensively used in clinical populations to evaluate the behavioral consequences of known or presumed structural or functional basal ganglia deficiencies: for example in schizophrenia ( Keri et al, 2000 ; Weickert et al, 2002 ; Foerde et al, 2008 ; Horan et al, 2008 ; Gomar et al, 2011 ; Karcher et al, 2019 ; Fernandez et al, 2021 ), Tourette syndrome ( Keri et al, 2002 ; Marsh et al, 2004 ), bulimia nervosa ( Labouliere et al, 2016 ), attention-deficit hyperactivity disorder ( Gabay and Goldfarb, 2017 ), Parkinson and Huntington diseases ( Knowlton et al, 1996a , b ; Shohamy et al, 2004a , b ), and children with acquired or developmental basal ganglia pathology ( Mayor-Dubois et al, 2010 ). Researchers have also used these tasks to assess memory capacities in individuals with neurodevelopmental disorders thought to be characterized by some procedural memory deficits, such as autism ( Brown et al, 2010 ; Obeid et al, 2016 ), obsessive–compulsive disorder ( Exner et al, 2014 ; Kelmendi et al, 2016 ; Hansmeier et al, 2018 ), specific language impairment ( Kemeny and Lukacs, 2010 ; Mayor-Dubois et al, 2014 ; Obeid et al, 2016 ), or developmental dyslexia ( Gabay et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have questioned the view that the WPT implicates primarily non-declarative learning and memory processes ( Knowlton et al, 1996a ; Poldrack et al, 2001 ; Gluck et al, 2002 ; Hopkins et al, 2004 ; Foerde et al, 2006 , 2007 ; Lagnado et al, 2006 ; Meeter et al, 2006 ; Newell et al, 2007 ; Price, 2009 ; Li et al, 2016 ), numerous studies evaluating the learning capacities of various clinical populations were conceived with the notion that the WPT assesses striatum-dependent or procedural learning. Indeed, the WPT or the Ice Cream Task, a modified version of the WPT in which participants must predict the flavor of ice cream preferred by a cartoon figure based on the different accessories worn by that figure ( Shohamy et al, 2004a ), have been extensively used in clinical populations to evaluate the behavioral consequences of known or presumed structural or functional basal ganglia deficiencies: for example in schizophrenia ( Keri et al, 2000 ; Weickert et al, 2002 ; Foerde et al, 2008 ; Horan et al, 2008 ; Gomar et al, 2011 ; Karcher et al, 2019 ; Fernandez et al, 2021 ), Tourette syndrome ( Keri et al, 2002 ; Marsh et al, 2004 ), bulimia nervosa ( Labouliere et al, 2016 ), attention-deficit hyperactivity disorder ( Gabay and Goldfarb, 2017 ), Parkinson and Huntington diseases ( Knowlton et al, 1996a , b ; Shohamy et al, 2004a , b ), and children with acquired or developmental basal ganglia pathology ( Mayor-Dubois et al, 2010 ). Researchers have also used these tasks to assess memory capacities in individuals with neurodevelopmental disorders thought to be characterized by some procedural memory deficits, such as autism ( Brown et al, 2010 ; Obeid et al, 2016 ), obsessive–compulsive disorder ( Exner et al, 2014 ; Kelmendi et al, 2016 ; Hansmeier et al, 2018 ), specific language impairment ( Kemeny and Lukacs, 2010 ; Mayor-Dubois et al, 2014 ; Obeid et al, 2016 ), or developmental dyslexia ( Gabay et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In sum, despite the fact that several studies have shown that the WPT does not necessarily assess striatal-dependent implicit memory in healthy young adults ( Knowlton et al, 1996a ; Poldrack et al, 2001 ; Gluck et al, 2002 ; Hopkins et al, 2004 ; Foerde et al, 2006 , 2007 ; Lagnado et al, 2006 ; Meeter et al, 2006 ; Newell et al, 2007 ; Price, 2009 ; Li et al, 2016 ), this task is still used to determine whether specific populations exhibit impairments of this memory system ( Knowlton et al, 1996b ; Keri et al, 2000 , 2002 ; Weickert et al, 2002 ; Marsh et al, 2004 ; Shohamy et al, 2004a , b ; Foerde et al, 2008 ; Horan et al, 2008 ; Brown et al, 2010 ; Kemeny and Lukacs, 2010 ; Mayor-Dubois et al, 2010 , 2014 ; Gomar et al, 2011 ; Exner et al, 2014 ; Gabay et al, 2015 ; Kelmendi et al, 2016 ; Labouliere et al, 2016 ; Obeid et al, 2016 ; Hansmeier et al, 2018 ; Karcher et al, 2019 ; Fernandez et al, 2021 ). Moreover, knowing that different learning strategies can lead to above chance performance in the WPT, it is fundamental to determine how participants solve the task ( Ashby and Maddox, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…The WPT (Knowlton et al, 1994) is a probabilistic learning task assessing procedural learning, which has been successfully used in a variety of neuropsychiatric diseases, ranging from bulimia nervosa (Labouliere et al, 2016), major depression (Mörkl et al, 2016), and schizophrenia (Fernandez et al, 2021; Gomar et al, 2011; Karcher et al, 2019) to attention‐deficit hyperactivity disorder (ADHD; Gabay & Goldfarb, 2017). The procedure of the WPT is described in detail in Supporting Information File S1.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, participants are not explicitly informed about the probabilistic nature of the task. Due to the probabilistic nature of the WPT, participants were originally considered to gradually acquire implicit knowledge about the cue-outcome associations across successive trials via striatum-dependent learning processes (e.g., Brown et al, 2010;Fernandez et al, 2021;Knowlton et al, 1994; but see Lagnado et al, 2006). Behavioral and neuroimaging studies, however, have provided evidence that the WPT implicates both hippocampus-dependent declarative processes and striatumdependent non-declarative processes (Foerde et al, 2006(Foerde et al, , 2007Gluck et al, 2002;Hopkins et al, 2004;Lagnado et al, 2006;Meeter et al, 2006;Newell et al, 2007;Poldrack et al, 2001;Price, 2009), with hippocampus-dependent processes being particularly prevalent in the early stages of learning.…”
Section: The Weather Prediction Taskmentioning
confidence: 99%
“…Behavioral and neuroimaging studies, however, have provided evidence that the WPT implicates both hippocampus‐dependent declarative processes and striatum‐dependent non‐declarative processes (Foerde et al., 2006, 2007; Gluck et al., 2002; Hopkins et al., 2004; Lagnado et al., 2006; Meeter et al., 2006; Newell et al., 2007; Poldrack et al., 2001; Price, 2009), with hippocampus‐dependent processes being particularly prevalent in the early stages of learning. Nevertheless, unduly influenced by the early reports purporting that the WPT specifically assessed striatal‐dependent procedural learning, many researchers have persisted in using the WPT and WPT‐like tasks for the explicit purposes of characterizing procedural learning and memory in typical and atypical development (e.g., Gabay & Goldfarb, 2017; Kemeny & Lukacs, 2010; Mayor‐Dubois et al., 2010, 2016), and the behavioral consequences of known or presumed structural or functional basal ganglia deficiencies in children and adults with, for example, attention‐deficit hyperactivity disorder (Gabay & Goldfarb, 2017), bulimia nervosa (Labouliere et al., 2016), schizophrenia (Fernandez et al., 2021; Foerde et al., 2008; Gomar et al., 2011; Horan et al., 2008; Karcher et al., 2019; Keri et al., 2000; Weickert et al., 2002), Parkinson and Huntington diseases (Knowlton, Mangels, et al., 1996; Knowlton, Squire, et al., 1996; Shohamy, Myers, Grossman, et al., 2004; Shohamy, Myers, Onlaor, et al., 2004), and Tourette syndrome (Keri et al., 2002; Marsh et al., 2004).…”
Section: Introductionmentioning
confidence: 99%